2019
DOI: 10.1002/cam4.2638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different doses of erythropoietin in patients with myelodysplastic syndromes: A propensity score‐matched analysis

Abstract: Background Erythropoiesis‐stimulating agents effectively improve the hemoglobin levels in a fraction of anemic patients with myelodysplastic syndromes (MDS). Higher doses (HD) of recombinant human erythropoietin (rhEPO) have been proposed to overcome suboptimal response rates observed in MDS patients treated with lower “standard doses” (SD) of rhEPO. However, a direct comparison between the different doses of rhEPO is lacking. Methods A cohort of 104 MDS patients treated with HD was retrospectively compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…However, it should be said that this study was conducted before the publication of the IWG criteria, so a strict comparison cannot be made. Recently, the FISM group published a retrospective propensity-matched cohort study comparing patients treated with standard-dose erythropoietin (i.e., 40,000 U/week) and high-dose erythropoietin (i.e., 40,000 U twice weekly), finding that in general, there are no differences in erythroid response rate between these two groups, except in transfusion dependence and patients with worse prognostic features, both of these not the target of our study [ 34 ]. However, the patients who applied the dose doubling had no or minimal increases in Hb levels when treated with a standard erythropoietin dose.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be said that this study was conducted before the publication of the IWG criteria, so a strict comparison cannot be made. Recently, the FISM group published a retrospective propensity-matched cohort study comparing patients treated with standard-dose erythropoietin (i.e., 40,000 U/week) and high-dose erythropoietin (i.e., 40,000 U twice weekly), finding that in general, there are no differences in erythroid response rate between these two groups, except in transfusion dependence and patients with worse prognostic features, both of these not the target of our study [ 34 ]. However, the patients who applied the dose doubling had no or minimal increases in Hb levels when treated with a standard erythropoietin dose.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were conducted in Europe (n = 24), and seven studies did not report the geographic location. Data sources were spread across nationwide registries, medical records in hospitals, Of the 38 studies identified (Table 2), one (3%) was a randomized controlled trial [22], three (8%) were non-randomized trials [23][24][25], 10 (26%) were single-arm trials [26][27][28][29][30][31][32][33][34][35], 15 (39%) were retrospective cohort studies [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], and four (11%) were prospective cohort studies [51][52][53][54]. One study (3%) was a compassionate, open-label, therapeutic trial [55], and four studies (11%) did not report the study design [56][57][58][59].…”
Section: Slrmentioning
confidence: 99%
“…Out of 16 studies, comparing age in ESA responders and non-responders, 14 reported univariate analyses and one study each reported results from bivariate [44] and a multivariate analysis [47] (Table S2). Of the 14 studies reporting univariate analyses, only two [36,48] reported statistically significant differences in age between responders and non-responders.…”
Section: Agementioning
confidence: 99%
“…In multiple real-life studies, the actual rate of response is in fact around 60% for the patients selected, according to the above criteria. Regarding the doses, it is generally accepted that the standard dose of ESAs is 30-40 U subcutaneously/week, while higher doses have been proposed, mainly by Italian researchers [11], without a significant impact on response, duration of response, or overall survival, apart for the group of patients with Hb 8-10 g/dL, with a diagnosis of MDS with unilineage erythroid dysplasia, MDS-RS, or del(5q) [12]. Interruption of treatment with ESAs almost always provokes loss of response.…”
Section: Therapymentioning
confidence: 99%
“…of patients with Hb 8-10 g/dL, with a diagnosis of MDS with unilineage erythroid dysplasia, MDS-RS, or del(5q) [12]. Interruption of treatment with ESAs almost always provokes loss of response.…”
Section: Therapymentioning
confidence: 99%